2006
DOI: 10.1038/sj.ki.5000371
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis and iodinated contrast media

Abstract: Contrast media are excreted mainly by glomerular filtration. There is thus, a significant correlation between both body and renal clearances of contrast media and glomerular filtration rate, and their renal excretion will be delayed in patients with renal insufficiency. Contrast media can be efficiently removed from blood by hemodialysis (HD). Since most contrast media are middle-sized molecules, the main factors potentially influencing their removal by HD are blood flow, membrane surface area, molecular size,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 36 publications
1
60
0
3
Order By: Relevance
“…Meanwhile, the rate of chronic dialysis at the time of discharge in salin group was 45% (Solomon etal., 2004). Nevertheless, other studies demonstrated that hemodialysis in patients with previous history of renal failure was not beneficial and the incidence of CIN will not be changed by this modality (Deray, 2006;Vogt, 2001).One meta-analysis has supported this result (Cruz etal., 2006). Patients on dialysis do not also need dialysis after contrast exposure (Hamani etal., 1998;Morcos etal., 2002).…”
Section: Renal Replacement Therapysupporting
confidence: 65%
See 1 more Smart Citation
“…Meanwhile, the rate of chronic dialysis at the time of discharge in salin group was 45% (Solomon etal., 2004). Nevertheless, other studies demonstrated that hemodialysis in patients with previous history of renal failure was not beneficial and the incidence of CIN will not be changed by this modality (Deray, 2006;Vogt, 2001).One meta-analysis has supported this result (Cruz etal., 2006). Patients on dialysis do not also need dialysis after contrast exposure (Hamani etal., 1998;Morcos etal., 2002).…”
Section: Renal Replacement Therapysupporting
confidence: 65%
“…Only few study reported the prophylactic usefulness of hemodialysis (Lee etal., 2007;McCullough & Soman, 2005). But repeatedly it has been shown that hemodialysis has no role in preventing CIN (Cruz etal., 2006;deray, 2006;Marenzi etal., 2006b). In contrast to positive studies one RCT showed that prophylactic dialysis caused more reduction of renal function and these patients need more dialysis after exposure to contrast (Vogt etal., 2001).…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…The first study was criticized for the methodological flaw using serum creatinine to evaluate the renal function and for the insufficient clearance of contrast with a low dosage of substitution solution [25]. Several potential reasons for the efficacy of CVVH, such as the use of heparin and biocarbonate-based solution, have been raised, but none of them seemed plausible.…”
Section: Discussionmentioning
confidence: 99%
“…There have a very high osmolality; however, because only small amounts (0.3 mL/kg of body weight) are injected for most studies compared with 1 to 2 mL/kg of body weight for iodinated contrast media, the systemic effect of osmolality is minimal. However, when these agents are used for radiograph attenuation rather than their magnetic properties (as in digital subtraction angiography), doses that are two to three times higher are required and nephrotoxicity (CIN) has been reported [22].…”
Section: Contrast Mediamentioning
confidence: 99%